An Development of an articulation test for bahdini kurdish preschool-age children - Salih, Rezheen; Hasan , Aveen (Humanities Journal of University of Zakho, 2022)
ABSTRACT Articulation tests record and analyze children’s speech and they are used to determine which sounds children can or cannot say or if the speech errors the children produce are developmentally appropriate or they are delayed. The aim of this study was to develop an articulation test for Bahdini Kurdish preschool children. For this purpose, a picture-naming test was designed to elicit spontaneous single-word responses representing 26 consonants in initial, medial and final positions and 8 vowels in medial positions. Seven experts were asked to review the test and complete a questionnaire. Then, it was presented to 65 normal Bahdini Kurdish speaking children. They were 38 males and 27 females from three different age groups: 3, 4, and 5 years old. The children’s responses were recorded and then scored for each correct utterance and picture identification. The results show that there are no significant differences among the experts’ responses which reflect their approval for the test to be a valid tool for collecting the phonetic inventory of the children. There is a significant and high correlation between correct word utterances and picture identification which prove the content validity of the test. Finally, there are no significant differences between males and females which indicates that the test is suitable for both genders, while significant differences were found among age groups in which old children performed better than younger ones. Thus, the test is a valid and a reliable tool that can be applied to collect the phonetic inventory of Bahdini Kurdish speaking children.